Moby dyke eaudiobook An obsessive quest to track down the last remaining lesbian bars in america. - Burton, Krista (Simon & Schuster Audio, 2023)
A former Rookie contributor and creator of the popular blog Effing Dykes investigates the disappearance of America's lesbian bars by visiting the last few in existence. Lesbian bars have always been treasured safe spaces for their customers, providing not only a good time but a shelter from societal alienation and outright persecution. In 1987, there were 206 of them in America. Today, only a couple dozen remain. How and why did this happen? What has been lost—or possibly gained—by such a decline? What transpires when marginalized communities become more accepted and mainstream? In Moby Dyke , Krista Burton attempts to answer these questions firsthand, venturing on an epic cross-country pilgrimage to the last few remaining dyke bars. Her pilgrimage includes taking in her first drag show since the onset of the pandemic at The Back Door in Bloomington, Indiana; competing in dildo races at Houston's Pearl Bar; and, despite her deep-seated hatred of karaoke, joining a group serenade at Nashville's Lipstick Lounge and enjoying the dreaded pastime for the first time in her life. While Burton sets out on the excursion to assess the current state of lesbian bars, she also winds up examining her own personal journey, from coming out to her Mormon parents to recently marrying her husband, a trans man whose presence on the trip underscores the important conversation about who precisely is welcome in certain queer spaces—and how they and their occupants continue to evolve. Moby Dyke is an insightful and hilarious travelogue that celebrates the kind of community that can only be found in windowless rooms soundtracked by Britney Spears-heavy playlists and illuminated by overhead holiday lights no matter the time of year.